2012
DOI: 10.1016/j.watres.2012.08.042
|View full text |Cite
|
Sign up to set email alerts
|

A novel bioelectrochemical BOD sensor operating with voltage input

Abstract: Biochemical oxygen demand (BOD) is a measure of biodegradable compounds in water and is, for example, a common parameter to design and assess the performance of wastewater treatment plants. The conventional method to measure BOD is time consuming (5 or 7 days) and requires trained personnel. Bioelectrochemical BOD sensors designed as microbial fuel cells (MFCs), which are systems where bacteria convert organic matter into an electrical current, have emerged as an alternative to the conventional technique. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 14 publications
1
43
0
4
Order By: Relevance
“…The high sensitivity of the MFC's performance to a number of environmental and biological factors make them suitable to act, in turn, as biosensors [21,107,108]. Therefore, properly combining energy generation and sensing functionalities from MFCs, self-powered devices, i.e., operated without any external electricity supply, can be designed to operate autonomously for remote detection and quantification of desired parameters [109,110].…”
Section: Mfc As a Self-powered Biosensor Versus A Traditional Whole-cmentioning
confidence: 99%
“…The high sensitivity of the MFC's performance to a number of environmental and biological factors make them suitable to act, in turn, as biosensors [21,107,108]. Therefore, properly combining energy generation and sensing functionalities from MFCs, self-powered devices, i.e., operated without any external electricity supply, can be designed to operate autonomously for remote detection and quantification of desired parameters [109,110].…”
Section: Mfc As a Self-powered Biosensor Versus A Traditional Whole-cmentioning
confidence: 99%
“…The lowest detection limit of the described biosensor was 10 μM acetate. In comparison to other microbial organic substrate determination methods, the method in this study is more sensitive, quicker (range from 5 to 20 h [15]), and does not require pure culture (e.g. bioluminescence-based test that required Pseudomonas fluorescens P17 of Spirillum sp.…”
Section: Standard Curves Recovery Time and Detection Limitsmentioning
confidence: 99%
“…Previous studies showed that a MFC acclimated to high AP produced higher current (30% more) than a MFC acclimated to a lower AP [15]. For maximum power production, the AP should be as low and the cathode potential as high as possible of a MFC [13].…”
Section: Increasing Sensitivity and Reducing Recovery Timementioning
confidence: 99%
“…This means apart from serving as an alternate power source for remote sensors, MFCs themselves may be used as sensors to detect many parameters Modin and Wilén 2012;Uríaa et al 2012). Though some reviews (Dewan et al 2014;Sun et al 2015) briefly mention MFC sensors with limited applications, this present review summarizes the latest developments in various biosensor applications using MFCs including monitoring microbial activity, testing BOD, detection of toxicants, detection of microbial biofilms that cause biocorrosion and some other unusual application.…”
Section: Introductionmentioning
confidence: 99%